Potential Natural Small Molecular Compounds for the Treatment of Chronic Obstructive Pulmonary Disease: An Overview - Li, Liu-Ying; Zhang, Chuan-Tao; Zhu, Feng-Ya; Zheng, Gang; Liu, Yu-Fei; Liu, Ke; Zhang, Chen-Hui; Zhang, Hong (Frontiers in Pharmacology, 2022)
Chronic obstructive pulmonary disease (COPD) is one of the major diseases threatening human life and health. According to the report released by the World Health Organization (WHO) in 2020, COPD has become the third leading cause of death in the world, featuring sustainable growth of incidence rate as well as population age. The purpose of this review focuses on the advancement of bioactive natural compounds, such as baicalin, quercetin, resveratrol and curcumin, which demonstrate promising therapeutic/interventional effects on CODP in vitro and in vivo. Information emphasizing on COPD was systematically collected from several authoritative internet database including Web of Science, PubMed, Elsevier, Wiley Online Library and Europe PMC, with a combination of keywords containing “COPD” and “natural small molecular compounds”. The new evidence indicated that these valuable molecules featured unique functions in the treatment of COPD through various of biological processes such as anti-inflammatory, anti-oxidant, anti-apoptosis and anti-airway fibrosis, etc. Moreover, we found that the promising effects of these natural compounds on COPD was mainly achieved through JAK3/STAT3/NF-κB and MAPK inflammatory signaling pathways, Nrf2 oxidative stress signaling pathway, TGF-β1/Smad 2/3 fibrosis signaling pathway, which referenced to multiple targets like TNF-α, IL-6, IL-8, TIMP-1, MMP, AKT, JAK3, IKK, PI3K, HO-1, MAPK，P38, ERK, etc. Current challenges and future directions in this promising field are also discussed at the end of this review. For the convenience of readers, this review is divided into ten parts according to the structures of potential natural small molecular compounds. We hope that this review could bring a quick look and provide some inspiration for the research of COPD.